Monetary Policy in Dollarized Economies - Bennett, Adam (Occasional Papers; Occasional Paper, 1999)
Dollarization - the holding by residents of a substantial portion of their assets in foreign-currency-denominated assets- is a common feature of developing and transition economies, and therefore typical of many countries with IMF - supported adjustment programs. This paper analyzes policy issues that arise-and various monetary strategies that may be pursued- when the monetary sector is dollarized, and it considers the implications that dollarization has for the design of IMF programs.